PsycEXTRA Dataset 2012
DOI: 10.1037/e502412013-188
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Constructive Processes and the Future of Memory

Abstract: Memory serves critical functions in everyday life, but is also prone to error. This article examines adaptive constructive processes, which play a functional role in memory and cognition but can also produce distortions, errors, or illusions. The article describes several types of memory errors that are produced by adaptive constructive processes, and focuses in particular on the process of imagining or simulating events that might occur in one's personal future. Simulating future events relies on many of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…As Bernecker (2010) concludes, the problem with the memory-markers thus far proposed is that "they don't offer a reliable mark" (p. 22). However, this need not concern us if memory is construed as a functionally related, interacting set of cognitive abilities rather than a fixed inscription in neural matter (e.g., De Brigard, 2013;Klein et al, 2004;Schacter, 2012). Memory and imagination may be so difficult to disentangle because there is no clear conceptual (e.g., Klein, 2013b;Schacter, 2012) or neurological (Mullally & Maguire, in press) line of demarcation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Bernecker (2010) concludes, the problem with the memory-markers thus far proposed is that "they don't offer a reliable mark" (p. 22). However, this need not concern us if memory is construed as a functionally related, interacting set of cognitive abilities rather than a fixed inscription in neural matter (e.g., De Brigard, 2013;Klein et al, 2004;Schacter, 2012). Memory and imagination may be so difficult to disentangle because there is no clear conceptual (e.g., Klein, 2013b;Schacter, 2012) or neurological (Mullally & Maguire, in press) line of demarcation.…”
Section: Discussionmentioning
confidence: 99%
“…Leading the way are Dan Schacter (2012;Schacter, Addis, Hassabis, Martin, Spreng, & Szpunar, 2012), Suddendorf and Corballis (2007), Hans Markowitsch (Markowitsch &Staniliou, 2011) andseveral others (e.g., De Brigard, 2013;Dudai & Carruthers, 2005;Howe, 2011). However, since the pioneering insights of Bradley (1887), the present paper is the first of which I know -with two important exceptions: Boyer (2009) 9 who, in discussion of the evolved functions of episodic recollection, presents ideas bearing a clear relation to those proposed herein, and Tulving (2005), whose ideas I present below -to take the next step and argue that memory, as designed by natural selection, is not simply capable of imagining the future; rather imagining the future is its evolved function, its raison d'être.…”
Section: Final Thoughtsmentioning
confidence: 99%
“…The capacity to mentally simulate events that might happen in one's personal futureoften referred to as episodic future thinking-has attracted growing interest in the past few years, probably due to the increasing recognition of its importance in the regulation of human behavior (Schacter, 2012;Seligman, Railton, Baumeister, & Sripada, 2013;Suddendorf & Corballis, 2007;Szpunar, 2010). Findings from cognitive, neuropsychological, and neuroimaging research have shown that episodic future thoughts are created based on informational components provided by episodic and semantic memory (i.e., specific past experiences and general knowledge about the world and the self), and multiple cognitive processes are engaged to retrieve, select, and assemble relevant pieces of information (for reviews, see D 'Argembeau, 2015;Irish & Piguet, 2013;Klein, 2013;Schacter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A second kind of evidence comes from studies showing that imagination can be easily confused with memory and that simply imagining that an experience might have occurred can lead to increased confidence that it actually occurred (10,(26)(27)(28)(29)(30). From an adaptive perspective, these findings may reflect, in part, the important role of memory in imagining future events (22,(31)(32)(33)(34)(35) and that memory and imagination depend, to a large extent, on similar underlying cognitive and neural processes (36).A third kind of evidence for adaptive-memory distortion comes from the well-known postevent misinformation effect, where people incorporate erroneous information encountered after an original event into their memory of the original event (2). From an adaptive perspective, the misinformation effect may arise as a byproduct of memory-updating processes, which normally serve to strengthen existing memory representations and to incorporate relevant new information (37, 38) but can contribute to distortions or false memories if novel information is confused with old information (3, 23).…”
mentioning
confidence: 99%